Mímesis y miniatura: la “metáfora viva” en las artes japonesas del “depaisaje” - Molina Barea, María del Carmen (Eikón / Imago, 2025)
This paper analyzes the key points of Japanese landscaping according to the concept of “dépaysage”, which is derived from avant-garde practices of poetic estrangement rooted in metaphor. Taking this as guiding principle there will be addressed Japanese aesthetic techniques -such as bonsai, suiseki and Zen gardens- so as to excavate the way in which they are metaphorized. It will be necessary to draw up a comparative research of the meanings of Aristotelian metaphor. Ultimately, the paper argues that resources located within Japanese dépaysement go beyond mimesis to develop poietic representations in line with the “live metaphor” coined by Paul Ricoeur.